2018
DOI: 10.1111/epi.13985
|View full text |Cite
|
Sign up to set email alerts
|

Mood disorders in familial epilepsy: A test of shared etiology

Abstract: SummaryObjective: Mood disorders are the most common comorbid conditions in epilepsy, but the cause remains unclear. One possible explanation is a shared genetic susceptibility to epilepsy and mood disorders. We tested this hypothesis by evaluating lifetime prevalence of mood disorders in relatives with and without epilepsy in families containing multiple individuals with epilepsy, and comparing the findings with rates from a general population sample. relative with FE. Compared with general population rates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…At last, the quality of life is likely to be worse in epilepsy patients with common mental disorders [39]. The present study showed that a family history of epilepsy was associated with mental illness which is consistent with other studies [40,41]. The commonest (27%) risk factors identified in the hospital-based retrospective study in Saudi Arabia was the presence of a family history of epilepsy [42].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At last, the quality of life is likely to be worse in epilepsy patients with common mental disorders [39]. The present study showed that a family history of epilepsy was associated with mental illness which is consistent with other studies [40,41]. The commonest (27%) risk factors identified in the hospital-based retrospective study in Saudi Arabia was the presence of a family history of epilepsy [42].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, epilepsy and mental illness may share a common genetic predisposition. This is supported by the magnitude of mood disorders that were found high among people living with epilepsy who had a relative with focal epilepsy [41]. Common mental disorders found to be higher in epilepsy patients and people with common mental disorders have been more likely to suffer from epilepsy [39].…”
Section: Discussionmentioning
confidence: 88%
“…Las comorbilidades psiquiátricas, incluidos los trastornos del estado de ánimo (3) , la ansiedad (4) y los trastornos psicóticos (5) , son frecuentes en la epilepsia y, a menudo, ocurren en tasas de 2 a 3 veces o más que en la población general sin epilepsia. Considerando los diferentes tipos de psicosis, las psicosis interictales representan en algunas publicaciones un 5,2 % de los casos, las que corresponden a epilepsias del lóbulo temporal corresponden al 7 % y las psicosis postictales al 2 % (6) .…”
Section: Desarrollo Epidemiologíaunclassified
“…Evidence has been found that seizures and mood disorders, including depression, may share the same genetic cause in some epilepsy patients. It is believed that modern antidepressants (SSRI, SNRI, noradrenergic, and specific serotonergic antidepressant-NaSSA) can be safely used in epilepsy; however, due to the lack of relevant studies, the evidence is still incomplete, especially in the case of mild depression [257][258][259][260][261][262][263][264][265][266][267][268][269][270][271]. The current knowledge of the biochemical and structural background of depression is wide, and the issue has been sufficiently recognized.…”
Section: Gladiolus Daleniimentioning
confidence: 99%